Star stuff : Carl Sagan and the mysteries of the cosmos - Sisson, Stéphanie Roth (Roaring Brook Press, 2014)
"A biography of Carl Sagan focusing on his childhood and culminating in the Voyager mission and the Golden Record"--Provided by publisher.